# Mathematics - Trigonometric Identities

Prove:

sinx + tanx = tanx (1 + cosx)

What I have so far:

LS:

= sinx + tanx
= sinx + (sinx / cosx)
= (sinx) (cosx) + sinx / cos
= tanx (cosx + sinx)

I don't know what to do now

1. 👍 0
2. 👎 0
3. 👁 415
1. Your second last line needs brackets, and the following line makes no sense

Why not work on the right side?

RS = tanx(1+cosx)
=tanx + tanxcosx after expanding
= tanx + (sinx/cosx)cosx
= tanx + sinx
= LS

1. 👍 0
2. 👎 0
2. My second last line:

(sinx) (cosx) + sinx
_________________________
cosx

When I did the right side, I get the same problem as the left side:

RS:

= tanx + (1 + cosx)
= (sinx / cosx) (1 + cosx)
= (1 + cosx) (cosx)
= (sinx) (1 + cosx)
_______________________
cosx
= (sinx) + (cosx)(sinx)
________________________
cosx

And ... my teacher wants everything in terms of cos and sin

1. 👍 0
2. 👎 0
3. RS = tanx(1+cosx)
=tanx + tanxcosx after expanding
= tanx + (sinx/cosx)cosx
= tanx + sinx
= LS

For this line "=tanx + tanxcosx after expanding", how did you get the second tanx from and what has happened to the addition sign?

1. 👍 0
2. 👎 0
4. from you second last line

(sinx) (cosx) + sinx
_________________________
cosx

= sinx[cosx + 1]/cosx , ....I took out a common factor

= tanx(cosx + 1)
= RS

You said "And ... my teacher wants everything in terms of cos and sin"

your teacher probably suggested changing everything to sines and cosines as you work your way through. Notice that is also what I did as I showed the steps.

I would never have restricted my students to use only a part of their trig knowledge, why not make use of all the relationships at your hand, picking the simplest way?

1. 👍 0
2. 👎 0
5. secx/sinx - sinx/cosx = cotx

1. 👍 0
2. 👎 0

## Similar Questions

1. ### Maths

If is a n acute angle and tanx=3 4 evaluate cosx-sinx cosx+sinx

2. ### Further maths

If x is an acute angle, tanx =3/4,evaluate coax _sinx÷cosx+sinx

3. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

4. ### Math (Calculus AB)

For x≠0, the slope of the tangent to y=xcosx equals zero whenever: (a) tanx=-x (b) tanx=1/x (c) sinx=x (d) cosx=x Please help. I have a final tomorrow and I am working diligently to understand every type of problem that may show

Prove that cscx / cosx = tanx + cotx

2. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

3. ### TRIGONOMETRY *(MATHS)

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

4. ### maths

proof that tanx + secx -1/tanx - secx+1 = 1+sinx/cosx

1. ### Calculus

determine the absolute extreme values of the function f(x)=sinx-cosx+6 on the interval 0

2. ### pre-calculus

How do I prove that sinx/sinx+cosx=tanx/1+tanx

3. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

4. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a